HOME VISITING SUPERVISION (HVS): AN ALTERNATIVE APPROACH TO INCREASE THE COMMITMENT OF ELEMENTARY TEACHERS IN REMOTE AREAS - Nugroho, Piter Joko (Faculty of Education Universitas Negeri Malang, 2017)
Education in remote areas with its problems and obstacles requires a special approach. The phenomena of lower motivated teachers in remote areas need supervisors and related stakeholders to make relevant breakthrough efforts to solve the problems. Home Visiting Supervision (HVS) is an alternative approach applied by school supervisors to handle problems of unmotivated teachers. The purposes of this study are to describe (1) basic consideration of HVS, (2) the involvement of related stakeholders, (3) the implementation mechanism of HVS, and (4the indicators of HVS implementation progress. This study used a qualitative approach with case study design, the area where the supervisors work, Kecamatan Miri Manasa, Kabupaten Gunung Mas, Central Kalimantan Province. The results of the study showed that (1) the basic consideration HVS: a) supervision is not effectively implemented during school hours because there are often many teachers not at school during working hours, b) the teachers still prioritize to fulfill personal needs rather than fulfill their professional work assignment, so that it is easier to meet them at home, rivers or in the rice fields, c) the supervision implementation can be reached if the teachers commitment have been established; (2) the stakeholders who applied the HVS are elementary school supervisors, principals, and community leaders; (3) the implementation mechanism of HVS: a) preparation stage, b) introduction/initial meeting stage, c) implementation/process of supervision stage, and d) last meeting/feedback meeting stage; (4) indicators of HVS progress: a) increase in the teachers’ discipline regarding being on time when coming to and leaving the school. b) Teaching Learning Process are applied in all class, c) there is good cooperations and respect between the leaders and colleagues, d) the teachers are willing to accept supervision from the principal and supervisor. Keywords: home visiting supervision, increasing the commitment, elementary teacher, remote area